The Effectiveness of Microlearning Video Implementation in Improving Understanding of Network Infrastructure Administration Subjects at SMK Muhammadiyah Parepare - Fathir Aditya (Fakultas Teknik, Universitas Negeri Makassar, 2025)
This study aims to determine the effectiveness of implementing microlearning videos in enhancing students' understanding of network infrastructure administration at SMK Muhammadiyah Parepare. The research method used is descriptive quantitative with a pretest-posttest design. The research population consisted of 12th-grade TKJ students in the even semester of the 2024/2025 academic year. The sample in this study involved 19 students. Data were collected using test instruments, student response questionnaires, student activity observation sheets, and lesson plan implementation observation sheets. Data were analyzed using descriptive quantitative techniques. The results showed that the average pretest score before using microlearning videos was 29.30, which increased to 74.74 in the posttest. The average normalized gain score was 0.65, indicating a moderate category (0.3 ≤ g < 0.7). Furthermore, 84.21 of students scored above the minimum passing grade (KKM). The students' activeness during the learning process using microlearning videos reached 86.09, categorized as very active based on observer assessments. Additionally, 77.19 of students gave a positive response to the use of microlearning videos, 4.39 responded negatively, and 18.42 were neutral. Based on these results, it can be concluded that the use of microlearning videos effectively improves students' understanding of the network infrastructure administration subject in the 12th-grade TKJ class at SMK Muhammadiyah Parepare.